(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
Yogyakarta’s natural tourism has become increasingly popular since the easing of the COVID-19 pandemic restrictions, with diverse destinations such as the Palace, the South Coast, and the Mount Merapi Museum. To support its world geopark qualification and meet the demand for educational tourism, the development of geology-based destinations is necessary. The Godean Ancient Volcano in Sleman offers significant potential for geotourism with scientific and educational value. Mapping results indicate that Godean is the remains of an ancient volcano in the form of a caldera, composed of extrusive igneous rocks, intrusions (basalt, andesite, dacite, microdiorite), and pyroclastic products such as tuff, lapilli, and pumice. Hydrothermal alteration with distinctive mineralogy indicates post-eruptive magmatic activity and the potential for economically valuable mineralization. The caldera landscape, displaying the remains of ancient volcanic eruptions, serves as a visual attraction and a means of interpreting geoscience. Through geotrail routes, interpretation boards, and the integration of local crafts, this area can be developed as a center for geological educational tourism. Supported by access to YIA Airport, this research will enhance the understanding of Godean’s geological evolution while creating sustainable geotourism opportunities for the local community.